1999
DOI: 10.1046/j.1365-2036.1999.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose ranitidine for the relief of heartburn

Abstract: The classic symptoms of episodic heartburn and regurgitation associated with over-indulgence are well known to a large segment of the population, and are the hallmark of gastro-oesophageal re¯ux disease (GERD).1 Approximately 30% of adults contacted in a large US survey reported having suffered heartburn, acid indigestion or sour stomach, common terms used with over-the-counter products, within the past month; more than 20% of these individuals reported experiencing heartburn at least once per day.2 Nearly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Conversely, no significant favourable effect was observed in non-infected dyspeptic patients. Using the same outcome criterion, a lower dose of omeprazole, 10 mg a day, and ranitidine given at a dose presently recommended for over the counter treatment of dyspeptic patients,4 were ineffective both in infected and non-infected patients. A favourable effect of omeprazole and ranitidine in non-infected patients cannot be totally excluded because a secondary outcome criterion (that is, complete disappearance of symptoms) appeared to be favourably affected by these two drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, no significant favourable effect was observed in non-infected dyspeptic patients. Using the same outcome criterion, a lower dose of omeprazole, 10 mg a day, and ranitidine given at a dose presently recommended for over the counter treatment of dyspeptic patients,4 were ineffective both in infected and non-infected patients. A favourable effect of omeprazole and ranitidine in non-infected patients cannot be totally excluded because a secondary outcome criterion (that is, complete disappearance of symptoms) appeared to be favourably affected by these two drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Ranitidine was given at the dose presently recommended for over the counter treatment 4. We intended to conduct the trial in a manner which most closely resembled routine clinical practice.…”
mentioning
confidence: 99%
“…In addition, several studies have demonstrated that approximately 30 % of NERD patients report symptom relief after receiving an H2RA twice daily for 4 weeks [11,12]. H 2 RAs are particularly helpful in relieving postprandial heartburn for up to 12 h [13]. They are also effective in preventing postprandial heartburn if given 30 min before a meal [14].…”
Section: Histamine Type 2 Receptor Antagonistsmentioning
confidence: 97%
“…Randomized controlled studies in adults with GERD and esophagitis have demonstrated superiority of ranitidine over placebo in symptom relief and healing of the esophageal mucosa. 1,10,11 In children, data are more limited. Although standard recommendations for pediatric ranitidine dosing have often been in the range of 2.5-3 mg/kg/dose twice or thrice daily, The North American Society of Pediatric Gastroenterology and Nutrition recently published guidelines for the management of pediatric GERD recommending a considerably higher dose of 4-10 mg/kg/day orally, 12 based largely on expert opinion because published data are so limited.…”
Section: Discussionmentioning
confidence: 99%